IDENTIFIKASI BENTUK, FUNGSI, DAN MAKNA REDUPLIKASI BAHASA SASAK DIALEK [A-A] DI DESA ANGGARAKSA KECAMATAN PRINGGABAYA - Deny Prasetiawan (MABASAN, 2014)
Commonly, language could be seen based on three perspectives, namely are form, function and meaning. Form is relating to the situation which supporting its role as a mean of communication. Various communication needs of the language users and their relationship to the value and meaning aspect are its role in a language form which functions as a mean of communication. Those three aspects are owned by every language in the world.The aim of this research is to identify form, function, and meaning of Sasak language (BS) reduplication of /a-a/ dialect in Anggaraksa village. This research applies qualitative descriptive since it tries to describe language phenomenon based on actual circumstances.The data are presented by using formal and informal method. Formal method is formulating method by using signs or symbols while informal method is formulating by using words including the use of technical terms. The result of the research shows that (1) in Anggaraksa village, there are four types of reduplication, namely are full reduplication, half reduplication, and reduplication with affixes; (2) reduplication found in Angara’s creates new words different with the base words, the change of form (singular, plural, base words, and affixes); (3)reduplication found in Angara’s village also change the word class such as noun to be adjective and other word classes (verb, adjective, noun, and numbers) ; (4) reduplication in Angara’s village also creates new meaning, such as the meaning of (many/much, varieties, qualitative, quantitative and prequency intensity, reciprocal, and correlative.